2018
DOI: 10.1007/s00520-018-4289-8
|View full text |Cite
|
Sign up to set email alerts
|

Family interactions in childhood leukemia: an exploratory descriptive study

Abstract: Regarding the findings of this study, it is expected that health system policymakers in the country, while striving to strengthen the positive aspect of changes in family relationships and interactions, will develop and execute operational, comprehensive, and society-based plans in order to eliminate the barriers and problems of relationships within the family, as well as in relation to the larger community, taking into consideration the family's cultural and social beliefs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
0
19
0
2
Order By: Relevance
“…In addition to cytogenetic abnormalities, the increased risk of ALL can be associated with different environmental factors. Several case-control studies have introduced heavy smoking, father's freelance job, exposure to low or moderate/high levels of pesticides, and obesity as the most common risk factors associated with the predisposition for ALL in children (Gholami et al, 2011;Moghaddasi et al, 2018;Mohammadi et al, 2018;Urayama et al, 2010). Among all enrolled cases in the current study, 52 (41.6%) were girls and 73 (58.4%) were boys.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In addition to cytogenetic abnormalities, the increased risk of ALL can be associated with different environmental factors. Several case-control studies have introduced heavy smoking, father's freelance job, exposure to low or moderate/high levels of pesticides, and obesity as the most common risk factors associated with the predisposition for ALL in children (Gholami et al, 2011;Moghaddasi et al, 2018;Mohammadi et al, 2018;Urayama et al, 2010). Among all enrolled cases in the current study, 52 (41.6%) were girls and 73 (58.4%) were boys.…”
Section: Discussionmentioning
confidence: 58%
“…Similar to other malignancies, ALL seems to be a multifactorial disease, and environmental and genetic factors interact with each other, playing a key role in its incidence (Eden, 2010). Several studies have demonstrated that environmental and genetic factors such as breastfeeding, keeping children in kindergarten, exposure to radiation, smoking, farm animals, and some inherited diseases (such as Fanconi anemia) can be associated with an increased risk for ALL in children (Gholami et al, 2011;Karimi et al, 2016;Moghaddasi et al, 2018;Mohammadi et al, 2018;Urayama et al, 2010). These findings suggest that knowing risk factors for childhood leukemia, especially ALL, is a crucial step in the prevention and reduction of ALL occurence in childhood.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature indicates that chronic and/or terminal illnesses in their children can impact their parents' spousal relationships in a mixture of negative [ 21 , 22 ] and overall positive [ 23 ] manner. Our findings were consistent with this, as some parents expressed increased strength in their marital relationships due to shared experiences of uncertainty and emotional isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, having more time as a caregiver and spending a greater number of hours taking care of the child were found to influence the caregiver’s proxy-report of QoL. This is because of the fact that, during the disease, affective bonds are created and strengthened over time, helping cope with the disease and to improve the child’s QoL (Moghaddasi et al, 2018; Vlachioti et al, 2016).…”
Section: Discussionmentioning
confidence: 99%